Metode Simple Additive Weighting (SAW) dalam pemberian Reward Berdasarkan Hasil Kerja Karyawan PT.Berkah - Yusran, Rio Rahmat; Yusran, Resadana (LPPM UNIKA Santo Thomas Medan, 2023)
Reward is a gift or appreciation to employees for having good achievements in completing work assignments. On average, each company gives rewards to employees according to predetermined rules. Rewording has different standards and criteria. The problems that occur in this study are errors that often occur in giving rewords to employees who have the ability to work compared to other employees, frequent selection of employees who are not on target, the system used still uses a manual system and requires a long time in the selection process. The Simple Additive Weighting (SAW) method is capable of completing awarding employees according to the alternative criteria and weight values used. The criteria used are absence, responsibility, work loyalty, discipline, work results. The final result obtained in the awarding of work results on behalf of Muhamad Hanafi with a final score of 0.95 which is in the highest ranking.